“Apart but Together”: Isolation, Connections and Affection Among the Members of Afro-Brazilian Religions During the Covid-19 Pandemic - Calvo, Daniela (International journal of Latin American religions, 2021)
What does social isolation mean for members of religious groups who constitute themselves as a family and who value meetings, physical contact and bodily experience? What strategies do they follow to face the loneliness that isolation entails? Since the middle of March 2020, when the World Health Organization (WHO) declared the risk of pandemic and the number of contagions of SARS-Cov-2 in Brazil was beginning to grow, most communities of Afro-Brazilian religions have adhered to social isolation in order to avoid contagion, protect their members and contribute to containing the progress of the pandemic among the population. The phrase “Apart but together”, which accompanies the shared intention of preserving life and the suspension of religious celebrations and meetings, is manifested in an intensification of virtual communications, in seminars, debates, prayers and rituals with online participation. Messages, posts, photos and videos reconstitute a network of relationships, care, affection and solidarity and reaffirm belongings and identities.